Reduced innate lymphoid cells in the endometrium of women with endometriosis. (19th October 2021) - Sugahara, Takuya; Tanaka, Yukiko; Hamaguchi, Masahide; Fujii, Maya; Shimura, Koki; Ogawa, Kanae; Mori, Taisuke; Kusuki, Izumi; Fukui, Michiaki; Kitawaki, Jo
Abstract: Problem: Innate lymphoid cells (ILCs), a recently discovered family of innate immune cells, are responsible for the early immune response, and control both innate and adapted immune system via cytokine secretion. The role of ILCs in endometriosis has not been investigated; therefore, here, we aimed to investigate how the proportion of ILCs changes in endometriosis. Method of study: The percentage of each ILC group in CD45 + cells was examined in the peripheral blood, peritoneal fluid, endometrium, and ovarian endometrioma obtained from women with and without endometriosis (ERB‐C‐1216) using flow cytometry. Results: Specimens were obtained from 19 women with endometriosis and 15 without endometriosis. In the endometrium, patients with endometriosis had lower proportion of ILC2 and 3 compared to control specimens (ILC2: .02±.01% vs .07±.03%; P < .05, ILC3: .31±.14% vs 1.10±.93%; P < .05). There was no significant change in the peripheral blood or the peritoneal fluid between the two groups. Additionally, ovarian endometrioma increased the proportion of ILCs (ILC1: .92±1.12%, ILC2: .08±.08%, ILC3: .70±.39%) compared to the endometrium samples of patients with endometriosis each with P < .05. Immunohistochemistry of IL‐1β and IL‐23, which are ILC3‐inducing factors, showed no significant change in the H‐score of the epithelium of the two groups, but a significant increase was found in ovarian endometrioma. Conclusion: The proportion of ILC2 and 3 was reduced in the endometrium of patients with endometriosis, and ILCs were increased in ovarian endometrioma. Our findings may indicate a new immunological approach to understand the pathophysiology of endometriosis. Abstract :